2023
DOI: 10.14336/ad.2023.0801
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorins: Missing Signals in Age-dependent Alteration of Neuromuscular Junctions and Skeletal Muscle Regeneration

Abstract: Skeletal muscle is characterized by a remarkable capacity to rearrange after physiological changes and efficiently regenerate. However, during aging, extensive injury, or pathological conditions, the complete regenerative program is severely affected, with a progressive loss of muscle mass and function, a condition known as sarcopenia. The compromised tissue repair program is attributable to the gradual depletion of stem cells and to altered regulatory signals. Defective muscle regeneration can severely affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 212 publications
0
1
0
Order By: Relevance
“…In the muscle, age-related differential expression of many genes (SEMA3F, SEMA3G, SEMA6A, PLXNC1, SEMA4C, SEMA6D, PLXNB2, SEMA4A, SEMA6C, PLXNA3, SEMA5A, SEMA6B, SEMA3B with FDR < 0.05) involved in the "semaphorin-plexin signaling pathway" was found. Recently, Fard et al have shown that specific semaphorin molecules are involved in skeletal muscle regeneration and neuromuscular junction (NMJ) remodeling [49]. Defects in NMJ formation and defective muscle regeneration can lead to age-related skeletal muscle atrophy, also known as sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…In the muscle, age-related differential expression of many genes (SEMA3F, SEMA3G, SEMA6A, PLXNC1, SEMA4C, SEMA6D, PLXNB2, SEMA4A, SEMA6C, PLXNA3, SEMA5A, SEMA6B, SEMA3B with FDR < 0.05) involved in the "semaphorin-plexin signaling pathway" was found. Recently, Fard et al have shown that specific semaphorin molecules are involved in skeletal muscle regeneration and neuromuscular junction (NMJ) remodeling [49]. Defects in NMJ formation and defective muscle regeneration can lead to age-related skeletal muscle atrophy, also known as sarcopenia.…”
Section: Discussionmentioning
confidence: 99%